NERACA AIR BENDUNGAN TERITIP KOTA BALIKPAPAN PROVINSI KALIMANTAN TIMUR - Prijanto, Dwi; Ismoyo, M. Janu (WAKTU, 2010)
In order to identify the requirement, balance and availability analysis of water balance in theTeritip Dam to fulfill the raw water required at administration region of the river basin of the teritipdam. Data which used in this study is Balikpapan’s hidroclimatology, Then the data analysed, toget 10 daily stream discharge with Model F.J. Mock. After got the result of analysis from the wateravailibility, then continued with dependable discharge analysis with Basic Moon method that useLogarithm Pearson type III distribution, and also tested with Smirnov kosmogorof test. We get the99 % dependable discharge from year 1983 up to year of 2007 from this calculation that representthe discharge inflow to the dam that represent the dam water availability. The amount of waterrequired is amount of water required in administration region staying Teritip Dam Basin, thatlocated at east Balikpapan District, for example ; Countryside Manggar, Countryside ManggarBaru, Countryside Lamaru, Countryside Teritip to fulfill domestic, industry and non-domestic waterrequirement untill year of 2015. The Result of this study indicate that the Terit ip Dam water supplycan supply the demand of Domestic, non-domestic, and industrial water requirement with 100%reliability, at 2010. The Teritip Dam water supply can supply the demand of Domestic, nondomestic,and industrial water requirement with 100% reliability, at 2011. The Teritip Dam watersupply can supply the demand of Domestic, non-domestic, and industrial water requirement with100% reliability, at 2012. The Teritip Dam water supply can only supply the demand of Domestic,non-domestic, and industrial water requirement with 83% reliability, at 2013. The Teritip Damwater supply can only supply the demand of Domestic, non-domestic, and industrial waterrequirement with 69% reliability at 2014 The Teritip Dam water supply can only supply thedemand of Domestic, non-domestic, and industrial water requirement with 61% at 2015.